Ethnic mobilisation and Kenya's foreign policy in the face of the international criminal court (ICC) - Shilaho, Westen K. (Faculty of Humanities, University of the Free State, 2016)
Until the issue of international criminal justice entered into Kenya’s politics, following the violently disputed 2007 elections, Kenya’s successive governments had never taken international diplomacy and foreign policy seriously or, at least, had never publicly appeared to do so. Never before had the two concepts been so ubiquitous in the country’s political lexicon as when the Mwai Kibaki government mobilised locally, continentally and globally in an attempt to torpedo two cases facing prominent Kenyans, the highest profile being Uhuru Kenyatta and William Ruto, at the International Criminal Court (ICC). Kibaki, and later his successor Kenyatta, aggressively canvassed for support on the international stage against the ICC. Kenya featured prominently in regional summits, African Union summits, at the United Nations Security Council (UNSC), and within the Assembly of States Parties (ASP) of the Rome Statute as it tried to make a no-holds-barred onslaught against the ICC. This article considers whether this show of diplomatic force, which resulted in Kenya extracting concessions from the ICC, was consistent with a well thought out and coherent foreign policy or a cynical reaction meant to rescue indicted persons from the grip of the international criminal justice.
Keywords: Kenya; Justice; Diplomacy; Foreign policy; Impunity; International Criminal Court; Plutocracy; Kleptocrat; Tribalism; Etnicity